Experience of an inland healthcare center: Round table conclusions, abstract Roman Arana Iñiguez - Lanterna, W; Arana Iñiguez, Roman (Cirugía del Uruguay, 1973)
The present work aims to demonstrate our experience in neurotraumatology at the Hospital Escuela del Litoral de Paysandú, It encompasses a population of around 100,000 inhabitants. Includes the conclusions and summary of the Round Table of the XXIII Congress on Treatments of brain injuries in the interior of the country